Slowing progression of idiopathic pulmonary fibrosis with pirfenidone: from clinical trials to real-life experience. (April 2014) - Cottin, Vincent; Wijsenbeek, M; Bonella, F; Vancheri, C
Idiopathic pulmonary fibrosis (IPF) is a rare, progressive, irreversible and eventually fatal fibrosing lung disease. Pirfenidone is the only approved therapy for reducing disease progression indicated in adult patients with mild to moderate IPF, which is considered the best attainable goal for a progressive and irreversible disease like IPF. Pirfenidone is an orally active, small molecule with antifibrotic and anti-inflammatory properties. Data from Phase III, randomized, double-blind, placebo-controlled trials have shown that pirfenidone reduces lung function decline and improves progression-free survival time. Pirfenidone is generally well tolerated, with the most commonly reported adverse events being gastrointestinal, dermatologic and hepatic (liver enzyme elevations) in nature. Pirfenidone was approved in Japan in 2008 and in the European Union in 2011. Since its approval in Japan, the European Union, Canada and South Korea, an increasing number of specialized centers have used it in clinical practice, confirming the tolerability profile as observed in clinical trials. With the advent of new potential drugs, combination therapy may be the way to treat patients with IPF in the future.